Departemen Periodonsia Fakultas Kedokteran Gigi Universitas Indonesia Jakarta, Indonesia - Ranny Rachmawati; Chaidar Masulili; Sri Lelyati C. Masulili; Fatimah Tadjoedin; Irene Sukardi (Journal of Dentomaxillofacial Science, 2011)
Splint is one of the therapies to support the periodontal healing; aims to stabilize the teeth so the occlusal load canbe distributed equally to all other teeth. Periodontal splint can be used temporarily or permanently. The removableframe partial denture can be functioned not only for replacing the missing teeth but also as permanent splint. Initialtherapy has been implemented to all cases on this report, consists of scaling, root planning, occlusal adjustment andsurgical therapy including curettage, flap operation, but apparently teeth mobility still existed. In order to supportthe periodontal tissue health, the frame of removable partial denture is needed as splint. It can be concluded thatimplementation of the removable partial denture with framework as splint to support the periodontal treatmentshould be provided after the initial and surgical therapy.